On the concept and characteristics of long-term contract - A. S. Panova (Russian Journal of Economics and Law, 2014)
Objective: to explore the concept and importance of long-term contract in the country’s economy. Methods: the dialectical method of cognition, systematic and logical methods, method of analysis and synthesis. Results: The study of the legal nature of long-term contracts was carried out, the general direction of development of the Civil code of the Russian Federation was determined concerning regulating the issues related to long-term supply contracts. Scientific novelty: The conclusions of the legal nature of long-term contract were made, the possibilities of long-term contract for the development of modern national economy were revealed, the recommendations on the amending the Russian Civil code with norms on a long term contract. Practical value: The obtained results can be used for carrying out economic and legal research relating to economic development and entrepreneurship in the economic practice of long-term contracts, and for reading courses in the disciplines of "Civil law", "Business law", "Commercial law".